Ragam Produk Olahan Temulawak Untuk Mendukung Keanekaragaman Pangan - Aniswatul Khamidah; Sri Satya Antarlina; Tri Sudaryono (Jurnal Penelitian dan Pengembangan Pertanian, 2017)
Temulawak or javanese ginger (Curcuma xanthorrihza Roxb) is a rhizome herb that has medical benefits for increasing appetite and as an anticholesterol, antiinflammatory, antianemia, antioxidant and antimicrobe. Curcuminoid, a yellow substance in temulawak, has many health benefits. Besides for medicine, temulawak is used for food industry material mainly as natural dyes in food. The main components of temulawak are starch (41.45%) and fiber (12.62%). Temulawak also contains essential oils (3.81%) and curcumin (2.29%). Temulawak can be processed into various food products such us dried chips/simplicia (for steeping herbs), flour, instant drink, cookies, sweets, noodles, crackers, stick, cake, dodol and jelly candy. This paper describes composition, benefits, post-harvest handling and a variety of food products of temulawak.Keywords: Javanese ginger, benefits, food product, food diversificationABSTRAKTemulawak (Curcuma xanthorrihza Roxb) termasuk golongan tanaman rempah yang memiliki manfaat untuk meningkatkan nafsu makan dan sebagai antikolesterol, antiinflamasi, antianemia, antioksidan, dan antimikroba. Kurkuminoid sebagai zat utama yang berwarna kuning dalam temulawak diketahui memiliki banyak manfaat bagi kesehatan. Selain digunakan untuk pengobatan, temulawak berpeluang dikembangkan dalam industri pangan, terutama sebagai pewarna alami dalam makanan. Komponen terbesar dalam temulawak adalah pati 41,45% dan serat 12,62%. Temulawak juga mengandung minyak atsiri 3,81% dan kurkumin 2,29%. Temulawak dapat dikembangkan menjadi berbagai produk olahan pangan, antara lain simplisia, tepung, pati, minuman instan, kue kering, manisan, mi, kerupuk, stek, cake, dodol, dan permen jeli. Makalah ini memaparkan kandungan rimpang temulawak, manfaat, penanganan pascapanen, dan berbagai produk olahan temulawak.Kata kunci: temulawak, manfaat, produk olahan, keanekaragaman pangan